Perbandingan Gaya Tolak Terhadap Hasil Tolak Peluru: (Pembelajaran Penjas Melalui Daring Di Masa Pandemi Covid-19 SMP 1 Sijuk Kabupaten Belitung) - Muchamad Ishak; Azhar Ramadhan; Asep Angga (Jurnal Master Penjas & Olahraga, 2021)
This study aims to compare the repulsion force between the obrein force and the spin force, this study uses a comparative causal research. The population in this study were all eighth grade students of SMP 1 Sijuk in the 2020/2021 academic year. Through purposive sampling technique, samples were obtained, namely the sample in this study was class VIII which collected 15 students. The design of this study uses a posttest only design, which is causal comparative. After completing the study, the group was given a posttest for data collection. The initial analysis used a hypothesis with the help of the SPSS24 (Statistical Product and Service Solution) computer program. The researcher's hypothesis test used the t-test (independent sample t-test). Based on the output of SPSS, the t-test (independent sample t-test) with a significant level of 0.04 with a lower limit determined at 0.05 was obtained count = 2.134 and ttable = 2.0484. The area of acceptance of H0 is if t count < 2.0484, it is clear that H0 is rejected. Thus it can be said that there is a comparison between the O'brien style and the Spin style, the Obrein style gives the best results on the learning outcomes of students of SMP 1 Sijuk, Belitung Regency.